Water-soluble fluorinated copolymers as highly sensitive 19F MRI tracers: From structure optimization to multimodal tumor imaging - Tunca Arın, Tuba Ayça; Havlíček, Dominik; Dorado Daza, Diego Fernando; Jirát-Ziółkowska, Natalia; Pop-Georgievski, Ognen; Jirák, Daniel; Sedlacek, Ondrej (Materials today. Bio, 2025)
Fluorine magnetic resonance imaging (19F MRI) using polymer tracers overcomes limitations of conventional proton MRI by offering enhanced specificity. However, the lack of systematic comparisons among fluorinated polymers has hindered rational tracer design. In this study, we synthesized an extensive library of water-soluble fluorinated copolymers by varying ratios of hydrophilic and fluorinated monomers and evaluated their 19F MRI properties to identify key structure-property relationships. Optimizing the hydrophilicity of the non-fluorinated comonomer increased fluorine content without compromising water solubility, thereby enhancing the MRI signal. Factors such as chemical structure, molecular interactions, and magnetic relaxation times also significantly influenced tracer performance. The optimized copolymer, poly((N-(2,2,2-trifluoroethyl)acrylamide)60-stat-(N-(2-hydroxyethyl)acrylamide)40), exhibited unprecedented 19F MRI sensitivity with detection limits below 1 mg mL-1, the highest reported to date. We demonstrated the tracer's potential through successful in vivo 19F MRI visualization of solid tumors in mouse models, highlighting its promise for advanced biomedical imaging applications.